Functionalized separator material, method for its preparation and use in lithium ion batteries

CN121546287BActive Publication Date: 2026-10-30广州融捷能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511782069.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-29
Publication Date
2026-10-30
Estimated Expiration
2045-11-29

AI Technical Summary

Technical Problem

在此,陶瓷涂层虽然起到耐热、防止短路等功能,但生产成本高、复杂的生产工艺和较低的离子电导率进一步阻碍了功能化隔膜材料的使用

Benefits of technology

从电池内部安全性能来说,稳定的界面相容性和较高的机械性能提高该隔膜的热稳定性能,防止隔膜在高温的条件下发生自我卷缩,改善电池在高温下的安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion batteries, in particular to a lithium ion battery diaphragm material and a preparation method and application thereof. The diaphragm material comprises a base film and a protective material layer on the base film; the protective material layer comprises a first protective material layer and a second protective material layer coated on the first protective material layer; the first protective material layer comprises at least one of silicate, borate, alumina and phosphate; and the second protective material layer comprises methyl methacrylate-fluorine-containing polysulfide lithium ion polymer or methyl methacrylate-fluorine-containing polyurethane lithium ion polymer. The diaphragm material provided has a significant intermolecular interaction with lithium salt anions, the interaction provides good interface compatibility while keeping a low swelling rate, and effectively inhibits the formation and growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and in particular to a lithium-ion battery separator material, its preparation method, and its application. Background Technology

[0002] In the internal system of a lithium-ion battery, the separator is used to isolate the positive and negative electrodes and provide ion transport channels, playing a decisive role in the internal safety of the lithium-ion battery. With the widespread application of lithium-ion batteries in electric vehicles, portable electronic devices, and other fields, the performance and functional requirements for separators are increasingly stringent. Taking power batteries as an example, the performance requirements of fast charging and fast discharging place high demands on the ionic conductivity and mechanical strength of the separator. If the separator cannot meet the high ionic conductivity requirements, it can lead to significant lithium plating and separator damage during fast charging and discharging, potentially causing safety accidents. The causes of these problems can be addressed through the following two methods: To address the thermal stability issue, researchers coated the membrane substrate with a ceramic material exhibiting excellent thermal stability. While this ceramic coating provides heat resistance and short-circuit prevention, its high production cost, complex manufacturing process, and low ionic conductivity further hinder the application of functionalized membrane materials.

[0003] While the ceramic coating can improve the thermal stability of the membrane, the actual coating process closes off the original ion transport channels on the membrane. Therefore, there is an urgent need to coat an additional functional layer to achieve a protective coating that combines thermal stability and high ionic conductivity. Summary of the Invention

[0004] To address the above technical challenges, this invention makes changes to the safety, stability, and ionic conductivity performance of the diaphragm, which is of great significance for promoting the sustainable development of electric vehicles and renewable energy storage technologies.

[0005] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a functionalized membrane material, comprising a base membrane and a protective material layer thereon; The protective material layer includes a first protective material layer and a second protective material layer; The first protective material layer includes at least one of silicates, borates, alumina, and phosphates; The second protective material layer comprises a lithium-ion polymer of methacrylic acid-fluorinated polysulfide or a lithium-ion polymer of methacrylic acid-fluorinated polyurethane.

[0006] Due to the structural characteristics of the functional groups in polar groups such as fluorine-containing, sulfonic acid, and carboxylic acid compounds, there are differences in the energy levels of their molecular orbitals. This results in a dense distribution of electron density on atoms that are prone to reaction, further enriching the ion transport channels. For these reasons, the coated separator can effectively promote the uniform flow of lithium ions, ensuring a uniform electric field distribution inside the battery, thereby enabling ions to intercalate and deintercalate in an orderly manner.

[0007] In the cyclic charging and discharging process of batteries, the coated separator material provided by this invention exhibits significant intermolecular interactions with lithium salt anions. This interaction maintains a low swelling ratio while providing good interfacial compatibility, effectively suppressing the formation and growth of lithium dendrites. To a certain extent, the technical solution of this invention can significantly reduce the risk of coating film detachment from the base film.

[0008] As a specific embodiment of the present invention, the first protective material layer includes boehmite and / or alumina.

[0009] In a specific embodiment of the present invention, the boehmite is linear with an aspect ratio of (5-10):1 and a particle size of 1-5 μm; the alumina is spherical with a particle size of 0.5-3 μm.

[0010] In a specific embodiment of the present invention, the base film is a polypropylene base film with a thickness of 12-20 μm, a porosity of 40-50%, and an average pore size of 0.1-0.3 μm.

[0011] In a specific embodiment of the present invention, the thickness of the first protective material layer is 1 to 3 μm.

[0012] In a specific embodiment of the present invention, the thickness of the second protective material layer is 2 to 5 μm.

[0013] As a specific embodiment of the present invention, the total thickness of the functionalized membrane material is 15-28 μm, the ionic conductivity is ≥1.5 mS / cm (25℃), the transverse shrinkage rate is ≤1.6% and the longitudinal shrinkage rate is ≤3.4% after heating at 105℃ for 2 hours, and there is no curling phenomenon.

[0014] Secondly, the present invention provides a method for preparing the above-mentioned functionalized membrane material, comprising the following steps: Dispersant 1 and the first protective material are added to water in S1. After stirring, the mixture is coated onto the surface of the base film and the moisture is dried to obtain a base film material covered with the first protective material. S2, the second protective material, and dispersant 2 are stirred and mixed, then coated onto the base film material that has been covered with the first protective material. After drying, the product is obtained.

[0015] As a specific embodiment of the present invention, step S1 specifically includes: adding 0.8 to 1.2 parts of dispersant 1 to 45 to 55 parts of water by weight, stirring and dispersing at 1200 rpm for 18 to 22 minutes; adding 25 to 35 parts of the first protective material, stirring and dispersing at 1500 rpm for 55 to 65 minutes to obtain a slurry of the first protective material; coating it onto the surface of the base film by gravure roller coating or narrow-slit extrusion coating, drying the moisture at 85 to 95°C to obtain a base film covering the first protective material layer.

[0016] As a specific embodiment of the present invention, step S2 specifically includes: adding 35-45 parts of the second protective material to 95-105 parts of dispersant 2 by mass, stirring and dispersing at 1000 rpm for 55-65 min to obtain a slurry of the second protective material; coating it onto the surface of the first protective material layer by slit coating, and vacuum drying at 80°C for 6-8 h to obtain a functionalized membrane material.

[0017] In a specific embodiment of the present invention, the solid content of the dispersant 2 is 35-45%.

[0018] As a specific embodiment of the present invention, the second protective material includes a methacrylic acid-fluorinated polysulfide lithium-ion polymer, which is prepared by a copper-mediated fluoroalkylthioacylation polymerization reaction.

[0019] As a specific embodiment of the present invention, the preparation method of the methacrylic acid-fluorinated polysulfide lithium-ion polymer includes the following steps: (1) Under the condition of dry copper powder, 2,4,6-tribromophenyl methacrylate solution was slowly added dropwise to the reaction and stirred; 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution was added and reacted; after washing and drying, polytrifluoroethoxy sulfide PTF-Li was obtained. (2) Dissolve PTF-Li, p-fluorophenol methacrylate and triethylene glycol monomethyl ether methacrylate from step (1) in organic solvent 1, and react with azobisisobutyronitrile as an initiator; wash and dry to obtain PMMA-PTF-Li; that is, methacrylate-fluorinated polysulfide lithium ion polymer.

[0020] As a specific embodiment of the present invention, the copper powder in step (1) needs to be activated.

[0021] As a specific embodiment of the present invention, the solvent of the 2,4,6-methacrylate tribromophenyl ester solution in step (1) is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide and chloroform.

[0022] As a specific embodiment of the present invention, the molar ratio of copper powder: 2,4,6-tribromophenyl methacrylate: 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt: PTF-Li: p-fluorophenol methacrylate: triethylene glycol monomethyl ether methacrylate is 1:(1.5~2.5):(1.1~1.3):1:(1.8~2.2):(1.8~2.2).

[0023] In a specific embodiment of the present invention, in the preparation of the methacrylic acid-fluorinated polysulfide lithium-ion polymer, the concentration of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution is 0.8-1.0 mol / L; the amount of the initiator azobisisobutyronitrile is 0.6-1.0 wt% of the total mass of PTF-Li, p-fluorophenol methacrylate, and triethylene glycol monomethyl ether methacrylate.

[0024] As a specific embodiment of the present invention, the solvent of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution in step (1) is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, toluene, benzene and xylene.

[0025] As a specific embodiment of the present invention, the concentration of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution is 0.8-1.0 mol / L.

[0026] As a specific embodiment of the present invention, the organic solvent 1 in step (2) includes: N,N-dimethylformamide and / or dimethyl sulfoxide.

[0027] As a specific embodiment of the present invention, the second protective material includes a methacrylic acid-fluorinated polysulfide lithium-ion polymer, which is prepared by a copper-mediated fluoroalkylthioacylation polymerization reaction.

[0028] As a specific embodiment of the present invention, the preparation method of the methacrylic acid-fluorinated polyurethane lithium-ion polymer includes the following steps: Under the condition of dry copper powder M1, a solution of p-bromophenol methacrylate was slowly added dropwise to the reaction mixture while stirring; a solution of 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt was added and the reaction was continued; after washing and drying, polyurethane fluoroether PUF-Li was obtained. In step M2, PUF-Li, p-fluorophenol methacrylate, and triethylene glycol monomethyl ether methacrylate from step M1 are dissolved in organic solvent 2, and reacted using azobisisobutyronitrile as an initiator; the mixture is then washed and dried to obtain PMMA-PUF-Li, i.e., methacrylate-fluorinated polysulfide lithium ion polymer.

[0029] As a specific embodiment of the present invention, the solvent for the p-bromophenol methacrylate solution in step M1 is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, and chloroform.

[0030] As a specific embodiment of the present invention, the solvent of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution in step M1 is at least one selected from dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, toluene, benzene and xylene.

[0031] As a specific embodiment of the present invention, the organic solvent 2 in step M2 includes: N,N-dimethylformamide and / or dimethyl sulfoxide.

[0032] As a specific embodiment of the present invention, the dispersant 1 includes: polyethylene glycol and / or polyvinylpyrrolidone.

[0033] As a specific embodiment of the present invention, the dispersant 2 includes at least one of sodium methylene bis(naphthalene) sulfonate, polyvinylpyrrolidone, and methylnaphthalene sulfonate formaldehyde condensate.

[0034] As a specific embodiment of the present invention, the molar ratio of copper powder: p-bromophenol methacrylate: 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt: PUF-Li: p-fluorophenol methacrylate: triethylene glycol monomethyl ether methacrylate is 1:(1.5~2.5):(1.1~1.3):1:(1.8~2.2):(1.8~2.2).

[0035] In a specific embodiment of the present invention, in the preparation of the methacrylic acid-fluorinated polyurethane lithium-ion polymer, the concentration of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution is 0.6-0.8 mol / L; the amount of the initiator azobisisobutyronitrile is 0.6-1.0 wt% of the total mass of PUF-Li, p-fluorophenol methacrylate, and triethylene glycol monomethyl ether methacrylate.

[0036] Thirdly, the present invention provides a lithium-ion battery comprising: the functionalized separator material described above or the functionalized separator material prepared by the above preparation method.

[0037] As a specific embodiment of the present invention, the DCR of a 5 Ah battery at 25°C @ 50% SOC is reduced by 5-10 mΩ; after 1000 charge-discharge cycles at 1C, the battery capacity retention rate is ≥87%.

[0038] Thirdly, the present invention provides the application of the above-mentioned functionalized membrane material or the functionalized membrane material prepared by the above-mentioned preparation method in lithium-ion batteries for electric vehicles and portable electronic devices.

[0039] This invention employs a coating-filling method to modify the coating layer, the diaphragm layer / coating layer pore interlayer with a coating layer having good chemical stability and high ionic conductivity.

[0040] Beneficial effects: From the perspective of battery internal safety performance, stable interface compatibility and high mechanical properties improve the thermal stability of the separator, prevent the separator from self-rolling under high temperature conditions, and improve the battery's safety performance at high temperatures.

[0041] From a battery performance perspective, the application of this coated separator not only optimizes the ion conduction path but also effectively alleviates polarization during battery charging and discharging, extending battery life. DCR results at 5 Ah and 25°C @ 50% SOC confirm that it reduces the DCR by at least 5-10 mΩ compared to similar uncoated separator materials.

[0042] Its unique structural design and material properties help maintain the stability of the battery's internal structure, ensuring excellent electrochemical performance even under long-term or high-load operating conditions, and avoiding performance degradation caused by uneven ion distribution. Furthermore, this coated separator may play a key role in improving battery safety performance; its stable interfacial compatibility and high mechanical properties enhance the separator's thermal stability, preventing self-curling under high-temperature conditions.

[0043] During cycling, the coated membrane material provided by this invention exhibits significant intermolecular interactions with lithium salt anions. This interaction maintains a low swelling ratio while providing good interfacial compatibility, effectively inhibiting the formation and growth of lithium dendrites. To a certain extent, the technical solution of this invention can significantly reduce the risk of coating film detachment from the base film. Detailed Implementation

[0044] Example 1 1. The preparation of PMMA-PTF-Li includes the following steps: (1) 1 mol of copper powder (particle size 50-100 mesh) was activated under vacuum at 120℃ for 3 h. Under nitrogen atmosphere protection, a dimethyl sulfoxide solution containing 2 mol of tribromophenyl 2,4,6-methacrylate (solvent volume was 8 times the mass of tribromophenyl 2,4,6-methacrylate) was slowly added dropwise to the activated copper powder. The mixture was stirred at 800 rpm at 25℃ for 1.5 h. Subsequently, a dimethyl sulfoxide solution of 0.8 mol / L of 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt (volume was 1.2 times the molar amount of tribromophenyl 2,4,6-methacrylate) was added. The temperature was raised to 130℃ and the mixture was stirred at 600 rpm for 24 h. The reaction product was then reacted sequentially with ethanol (3 times, each time the volume was 5 times the mass of the product), deionized water (3 times, each time the volume was 5 times the mass of the product), and saturated saline solution (2... Wash the product (each time using 3 times the product mass), and vacuum dry at 50℃ for 12 hours to obtain PTF-Li.

[0045] (2) Dissolve 1 mol PTF-Li, 2 mol p-fluorophenol methacrylate, and 2 mol triethylene glycol monomethyl ether methacrylate in N,N-dimethylformamide (the amount of solvent used is 10 times the total mass of the three), add 0.6 wt% of azobisisobutyronitrile, and stir at 500 rpm for 24 h at 60 °C under a nitrogen atmosphere; wash the reaction product three times with N,N-dimethylformamide (each time the amount used is 6 times the mass of the product), and dry under vacuum at 60 °C for 24 h to obtain PMMA-PTF-Li.

[0046] 2. Preparation of functionalized membrane materials, including the following steps: S1. By mass, add 1 part of dispersant 1 (polyvinylpyrrolidone K30) to 50 parts of deionized water and stir and disperse at 1200 rpm for 20 min; add 30 parts of the first protective material (linear boehmite, aspect ratio 7:1, particle size 2-3 μm) and stir and disperse at 1500 rpm for 60 min to obtain boehmite slurry; use gravure roller coating (coating speed 5 m / min, coating pressure 0.3 MPa) to coat the slurry onto the surface of a 16 μm thick polypropylene base film (porosity 45%, average pore size 0.2 μm), and dry the moisture with hot air at 90℃ (air velocity 2 m / s, drying time 15 min) to obtain a base film material covered with a 2 μm thick boehmite layer.

[0047] S2 By weight, 40 parts of PMMA-PTF-Li were added to 100 parts of dispersant 2 (methylnaphthalenesulfonic acid formaldehyde condensate, solid content 40%), and the mixture was stirred and dispersed at 1000 rpm for 60 min to obtain a polymer slurry. The slurry was coated onto the boehmite layer surface of the above base membrane material by slit coating (coating speed 4 m / min, slit width 0.1 mm), and vacuum dried at 80℃ for 6 h (vacuum degree -0.09 MPa) to obtain the functionalized membrane material.

[0048] Performance testing: The functionalized membrane material has a total thickness of 21 μm, an ionic conductivity of 1.7 mS / cm (25℃), a tensile strength of 18 MPa, and a transverse shrinkage rate of 1.3% and a longitudinal shrinkage rate of 3.1% after heating at 105℃ for 2 hours, with no curling phenomenon. Lithium-ion battery performance test: After assembling a 5Ah lithium-ion battery, the DCR is 27mΩ at 25℃ and 50% SOC (35mΩ for the uncoated control sample), and the capacity retention rate is 88% after 1000 cycles.

[0049] Example 2 1. The preparation of PMMA-PUF-Li includes the following steps: M1: 1 mol of copper powder (particle size 50-100 mesh) was activated under vacuum at 120℃ for 3 h. Under a nitrogen atmosphere, a chloroform solution containing 2 mol of p-bromophenol methacrylate (the solvent volume was 7 times the mass of p-bromophenol methacrylate) was slowly added dropwise to the activated copper powder. The mixture was stirred at 700 rpm at 25℃ for 1 h. A toluene solution of 0.6 mol / L of 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt (the volume was 1.1 times the molar amount of p-bromophenol methacrylate) was added, and the mixture was heated to 130℃ and stirred at 550 rpm for 24 h. The reaction product was washed successively with ethanol (3 times, each time with a volume of 4 times the product mass), deionized water (3 times, each time with a volume of 4 times the product mass), and saturated brine (2 times, each time with a volume of 3 times the product mass). The product was then dried under vacuum at 50℃ for 12 h to obtain PUF-Li.

[0050] M2 dissolved 1 mol PUF-Li, 2 mol p-fluorophenol methacrylate, and 2 mol triethylene glycol monomethyl ether methacrylate in dimethyl sulfoxide (the amount of solvent used was 9 times the total mass of the three). 0.8 wt% of azobisisobutyronitrile was added, and the mixture was stirred at 450 rpm at 60 °C for 24 h under a nitrogen atmosphere. The reaction product was washed three times with dimethyl sulfoxide (each time with an amount 5 times the mass of the product), and then dried under vacuum at 60 °C for 24 h to obtain PMMA-PUF-Li.

[0051] 2. Preparation of functionalized membrane materials, including the following steps: S1. By weight, add 1 part dispersant 1 (polyethylene glycol PEG20000) to 50 parts deionized water and stir and disperse at 1200 rpm for 20 min; add 30 parts of the first protective material (spherical alumina, particle size 1-2 μm) and stir and disperse at 1500 rpm for 60 min to obtain an alumina slurry; use a narrow-slit extrusion coating method (coating speed 6 m / min, extrusion pressure 0.4 MPa) to coat the slurry onto the surface of a 14 μm thick polypropylene base film (porosity 42%, average pore size 0.18 μm), and dry the moisture with hot air at 85℃ (wind speed 1.8 m / s, drying time 12 min) to obtain a base film material covered with a 1.5 μm thick alumina layer.

[0052] S2, by mass, 40 parts of PMMA-PUF-Li were added to 100 parts of dispersant 2 (polyvinylpyrrolidone K90, solid content 35%), and the mixture was stirred and dispersed at 1000 rpm for 60 min to obtain a polymer slurry; the slurry was coated onto the surface of the alumina layer using a slit coating method (coating speed 4.5 m / min, slit width 0.08 mm), and vacuum dried at 80℃ for 6 h (vacuum degree -0.09 MPa) to obtain the functionalized membrane material.

[0053] 3. Performance testing: The total thickness of this functionalized membrane material is 18μm, the ionic conductivity is 1.6mS / cm (25℃), the tensile strength is 17MPa, and after heating at 105℃ for 2 hours, the transverse shrinkage rate is 1.6% and the longitudinal shrinkage rate is 3.4%, with no curling. 4. Lithium-ion battery performance test: 5Ah battery DCR 28mΩ (comparison sample 36mΩ), capacity retention rate 87% after 1000 cycles.

[0054] Example 3 1. The preparation of PMMA-PTF-Li includes the following steps: (1) 1 mol of copper powder (particle size 50~100 mesh) was activated under vacuum at 120℃ for 3 h (vacuum degree -0.095MPa). Under nitrogen atmosphere protection, a solution of 1,2-dichloroethane containing 2 mol of tribromophenyl 2,4,6-methacrylate was slowly added dropwise to the activated copper powder (the amount of solvent was 9 times the mass of tribromophenyl 2,4,6-methacrylate). The mixture was stirred at 850 rpm at 25℃ for 2 h. Then, a solution of 1.0 mol / L of dimethyl sulfoxide of 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt was added (the amount of solvent was 1.3 times the molar amount of tribromophenyl 2,4,6-methacrylate). The mixture was heated to 130℃ and stirred at 650 rpm for 24 h. The reaction product was then reacted with ethanol (3 times, each time the amount was 6 times the mass of the product) and deionized water (3 times, each time the amount was 6 times the mass of the product). The product was washed with saturated brine (twice, each time the amount was 4 times the mass of the product) and vacuum dried at 50°C for 12 hours (vacuum degree -0.09MPa) to obtain PTF-Li.

[0055] (2) Dissolve 1 mol PTF-Li, 2 mol p-fluorophenol methacrylate, and 2 mol triethylene glycol monomethyl ether methacrylate in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 1:1, total amount is 11 times the total mass of the three), add 1.0 wt% of azobisisobutyronitrile, and stir at 550 rpm for 24 h at 60 °C under nitrogen atmosphere; wash the reaction product three times with the above mixed solvent (each time the amount is 7 times the mass of the product), and vacuum dry at 60 °C for 24 h (vacuum degree -0.09 MPa) to obtain PMMA-PTF-Li.

[0056] 2. Preparation of functionalized membrane materials, including the following steps: S1. By weight, add 1 part of dispersant 1 (polyvinylpyrrolidone K30 and polyethylene glycol PEG20000 in a mass ratio of 1:1) to 50 parts of deionized water and stir and disperse at 1200 rpm for 20 min; add 30 parts of the first protective material (linear boehmite, aspect ratio 5:1, particle size 1-2 μm + spherical alumina, particle size 0.5-1 μm, mass ratio 1:1) and stir and disperse at 1500 rpm for 60 min to obtain a mixed slurry; use gravure roller coating (coating speed 5.5 m / min, coating pressure 0.35 MPa, gravure cell depth 5 μm) to coat the slurry onto the surface of an 18 μm thick polypropylene base film (porosity 48%, average pore size 0.25 μm), and dry the moisture with hot air at 95℃ (wind speed 2.2 m / s, drying time 18 min) to obtain a base film material covered with a 2.5 μm thick mixed protective layer.

[0057] S2. By weight, 40 parts of PMMA-PTF-Li were added to 100 parts of dispersant 2 (sodium methylene bis(naphthalene) sulfonate, solid content 45%), and the mixture was stirred and dispersed at 1000 rpm for 60 min to obtain a polymer slurry. The slurry was coated onto the surface of the mixed protective layer of the above base membrane material using a slit coating method (coating speed 4.2 m / min, slit width 0.12 mm, coating pressure 0.2 MPa), and vacuum dried at 80 °C for 6 h (vacuum degree -0.09 MPa) to obtain the functionalized membrane material.

[0058] 3. Performance testing: The total thickness of this functionalized diaphragm material is 25μm, the ionic conductivity is 1.8mS / cm (25℃), the tensile strength is 19MPa, and after heating at 105℃ for 2h, the transverse shrinkage rate is 1.2% and the longitudinal shrinkage rate is 2.9%, with no curling phenomenon. Lithium-ion battery performance testing: A 5Ah lithium-ion battery assembled using this separator had a DCR of 26mΩ under 25℃ and 50% SOC conditions (the DCR of the same specification battery without a protective material layer was 34mΩ), a reduction of 8mΩ; after 1000 charge-discharge cycles at 1C, the battery capacity retention rate was 89%, and the coulombic efficiency remained stable at over 99.5%.

[0059] Example 4 1. The preparation of PMMA-PUF-Li includes the following steps: M1. 1 mol of copper powder (particle size 50-100 mesh) was activated under vacuum at 120℃ for 3 h (vacuum degree -0.095 MPa). Under a nitrogen atmosphere, a dimethyl sulfoxide solution containing 2 mol of p-bromophenol methacrylate (solvent volume 8.5 times the mass of p-bromophenol methacrylate) was slowly added dropwise to the activated copper powder. The reaction was stirred at 750 rpm at 25℃ for 1.5 h. Then, a 0.7 mol / L dimethyl sulfoxide solution of 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt (volume 1.2 times the molar amount of p-bromophenol methacrylate) was added, and the temperature was raised to 130℃. The reaction was stirred at 600 rpm for 24 h. The reaction product was then successively diluted with ethanol (3 times, each time 5.5 times the product mass), deionized water (3 times, each time 5.5 times the product mass), and saturated saline solution (2 times, each time 3.5 times the product mass). The product was washed (times) and dried under vacuum at 50°C for 12 hours (vacuum degree -0.09MPa) to obtain PUF-Li.

[0060] M2 dissolved 4 mol PUF-Li, 2 mol p-fluorophenol methacrylate, and 8 mol triethylene glycol monomethyl ether methacrylate in dimethyl sulfoxide (the amount of solvent used was 10 times the total mass of the three). 0.7 wt% of azobisisobutyronitrile was added, and the mixture was stirred at 500 rpm at 60 °C for 24 h under a nitrogen atmosphere. The reaction product was washed three times with dimethyl sulfoxide (each time with an amount 6 times the product mass) and dried under vacuum at 60 °C for 24 h (vacuum degree -0.09 MPa) to obtain PMMA-PUF-Li.

[0061] 2. Preparation of functionalized membrane materials, including the following steps: S1. By weight, add 1 part dispersant 1 (polyethylene glycol PEG20000) to 50 parts deionized water and stir and disperse at 1200 rpm for 20 min; add 30 parts of the first protective material (spherical alumina, particle size 2-3 μm) and stir and disperse at 1500 rpm for 60 min to obtain an alumina slurry; use a narrow-slit extrusion coating method (coating speed 6.2 m / min, extrusion pressure 0.45 MPa, narrow slit width 0.15 mm) to coat the slurry onto the surface of a 15 μm thick polypropylene base film (porosity 44%, average pore size 0.22 μm), and dry the moisture with hot air at 90℃ (wind speed 2.0 m / s, drying time 16 min) to obtain a base film material covered with an 1.8 μm thick alumina layer.

[0062] S2. By mass, 40 parts of the above-mentioned PMMA-PUF-Li were added to 100 parts of dispersant 2 (polyvinylpyrrolidone K90, solid content 38%), and the mixture was stirred and dispersed at 1000 rpm for 60 min to obtain a polymer slurry. The slurry was coated onto the alumina layer surface of the above-mentioned base membrane material using a slit coating method (coating speed 4.8 m / min, slit width 0.1 mm, coating pressure 0.25 MPa), and vacuum dried at 80 °C for 6 h (vacuum degree -0.09 MPa) to obtain a functionalized membrane material.

[0063] 3. Performance testing: The total thickness of this functionalized membrane material is 20μm, the ionic conductivity is 1.7mS / cm (25℃), the tensile strength is 18.5MPa, and after heating at 105℃ for 2h, the transverse shrinkage rate is 0.6% and the longitudinal shrinkage rate is 0.8%, with no curling phenomenon. Lithium-ion battery performance testing: After assembling a 5Ah lithium-ion battery, the DCR was tested at 25℃ and 50% SOC, which was 25mΩ (the DCR of the same specification battery without a protective material layer was 33mΩ), a decrease of 8mΩ; after 1000 charge-discharge cycles at 1C, the battery capacity retention rate was 90%, and the coulombic efficiency was stable at over 99.6%.

[0064] Comparative Example 1 1. Preparation of PMMA-PUF-Li: Same as steps M1 to M2 in Example 2.

[0065] 2. Preparation of diaphragm material: By mass, 40 parts PMMA-PUF-Li, 1 part polyethylene glycol PEG20000, and 30 parts spherical alumina (particle size 1-2 μm) were added to 100 parts dispersant 2 (polyvinylpyrrolidone K90, solid content 35%). The mixture was stirred and dispersed at 1000 rpm for 60 min (with ultrasonic-assisted dispersion for 5 min every 15 min during the dispersion process, ultrasonic power 300 W) to obtain a mixed slurry. The slurry was directly coated onto the surface of a 16 μm thick polypropylene base membrane (porosity 45%, average pore size 0.2 μm) using a slit coating method (coating speed 5 m / min, slit width 0.12 mm, coating pressure 0.3 MPa). The membrane was then vacuum dried at 80℃ for 6 h (vacuum degree -0.09 MPa) to obtain a single-layer mixed coating diaphragm material (total coating thickness 5 μm).

[0066] 3. Performance testing: The membrane material has a total thickness of 21 μm, an ionic conductivity of 1.0 mS / cm (25℃), a tensile strength of 12 MPa, and exhibits obvious shrinkage after heating at 105℃ for 2 hours (transverse shrinkage rate of 8% and longitudinal shrinkage rate of 18%). Lithium-ion battery performance testing: After assembling a 5Ah lithium-ion battery, the DCR was tested at 25℃ and 50% SOC, and was 34mΩ (the DCR of the same specification battery without a protective material layer was 36mΩ), a decrease of only 2mΩ; after 1000 charge-discharge cycles at 1C, the battery capacity retention rate was 72%. During the cycle, due to lithium dendrite growth, a voltage jump occurred after the 500th cycle (from 3.7V to below 2.0V).

[0067] Comparative Example 2 1. By weight, add 1 part dispersant 1 (polyethylene glycol PEG20000) to 50 parts deionized water and stir and disperse at 1200 rpm for 20 min; add 30 parts linear boehmite (length-to-diameter ratio 7:1, particle size 2-3 μm) and stir and disperse at 1500 rpm for 60 min (ultrasonic dispersion for 5 min every 20 min, ultrasonic power 300W) to obtain boehmite slurry; use gravure roller coating (coating speed 5.5 m / min, coating pressure 0.35 MPa, gravure cell depth 3 μm) to coat the slurry onto the surface of a 16 μm thick polypropylene base film (porosity 45%, average pore size 0.2 μm), and dry the moisture with hot air at 90℃ (wind speed 2 m / s, drying time 15 min) to obtain a membrane material with only a 1.5 μm thick boehmite layer.

[0068] 2. Performance testing: The membrane material has a total thickness of 18μm, an ionic conductivity of 0.8mS / cm (25℃), a tensile strength of 13MPa, and exhibits shrinkage after heating at 105℃ for 2 hours (transverse shrinkage rate of 8% and longitudinal shrinkage rate of 15%). Lithium-ion battery performance testing: After assembling a 5Ah lithium-ion battery, the DCR was tested at 25℃ and 50% SOC, and was 33mΩ (the DCR of the same specification battery without a protective material layer was 36mΩ), a decrease of only 3mΩ; after 1000 charge-discharge cycles at 1C, the battery capacity retention rate was 75%. In the later stages of the cycle, due to the poor compatibility between the separator and the electrode interface, the charge-discharge plateau voltage difference increased (from the initial 0.1V to 0.5V).

[0069] Comparative Example 3 1. Preparation of membrane material: By weight, add 1 part dispersant 1 (polyethylene glycol PEG20000) to 50 parts of deionized water and stir and disperse at 1200 rpm for 20 min; add 30 parts of spherical alumina (particle size 1-2 μm) and stir and disperse at 1500 rpm for 60 min (ultrasonic dispersion for 5 min every 20 min, ultrasonic power 300W) to obtain alumina slurry; use narrow-slit extrusion coating method (coating speed 6 m / min, extrusion pressure 0.4 MPa, narrow slit width 0.15 mm) to coat the slurry onto the surface of a 16 μm thick polypropylene base membrane (porosity 45%, average pore size 0.2 μm), and dry the moisture with hot air at 90℃ (wind speed 2 m / s, drying time 15 min) to obtain a membrane material with only a 2 μm thick alumina layer.

[0070] 2. Performance testing: The membrane material has a total thickness of 19μm, an ionic conductivity of 0.9mS / cm (25℃), a tensile strength of 14MPa, and exhibits shrinkage after heating at 105℃ for 2 hours (transverse shrinkage rate of 7% and longitudinal shrinkage rate of 11%). Lithium-ion battery performance testing: After assembling a 5Ah lithium-ion battery, the DCR was tested at 25℃ and 50% SOC, and was 32mΩ (the DCR of the same specification battery without a protective material layer was 36mΩ), a decrease of only 4mΩ; after 1000 charge-discharge cycles at 1C, the battery capacity retention rate was 78%. During the cycle, due to uneven ion transport, the battery internal resistance gradually increased (from the initial 25mΩ to over 100mΩ).

[0071] Table 1 Thermal stability performance of Examples 1-4 and Comparative Examples 1-3 (heated at 105°C for 2 hours)

[0072] Therefore, Examples 1-4 demonstrate that the technical solutions of the present invention can effectively solve the problems related to ionic conductivity and thermal safety.

Claims

1. A functionalized membrane material, characterized in that, Including the base film and the protective material layer thereon; The protective material layer includes a first protective material layer and a second protective material layer coated on the first protective material layer; The first protective material layer includes at least one of silicates, borates, alumina, and phosphates; The second protective material layer includes PMMA-PTF-Li or PMMA-PUF-Li; The preparation method of the PMMA-PTF-Li includes the following steps: (1) Under the condition of dry copper powder, 2,4,6-methacrylate tribromophenyl ester solution was added dropwise and the reaction was stirred; 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution was added and stirring was continued; after washing and drying, polytrifluoroethoxy sulfide PTF-Li was obtained. (2) Dissolve the PTF-Li, p-fluorophenol methacrylate, and triethylene glycol monomethyl ether methacrylate from step (1) in organic solvent 1, and react with azobisisobutyronitrile as an initiator; wash and dry to obtain PMMA-PTF-Li; The preparation method of the PMMA-PUF-Li includes the following steps: Under the condition of dry copper powder M1, p-bromophenol methacrylate solution was added dropwise and the reaction was stirred; 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution was added and stirring was continued; after washing and drying, polyurethane fluoroether PUF-Li was obtained. In step M2, PUF-Li, p-fluorophenol methacrylate, and triethylene glycol monomethyl ether methacrylate from step M1 are dissolved in organic solvent 2, and reacted using azobisisobutyronitrile as an initiator; the mixture is then washed and dried to obtain PMMA-PUF-Li.

2. The functionalized membrane material according to claim 1, characterized in that, The first protective material layer comprises boehmite and / or alumina; And / or, the base film is a polypropylene base film with a thickness of 12-20 μm, a porosity of 40-50%, and an average pore size of 0.1-0.3 μm; And / or, the thickness of the first protective material layer is 1 to 3 μm; And / or, the thickness of the second protective material layer is 2 to 5 μm; And / or, the total thickness of the functionalized membrane material is 15-28 μm, the ionic conductivity at 25°C is ≥1.5 mS / cm, the transverse shrinkage rate is ≤1.6% and the longitudinal shrinkage rate is ≤3.4% after heating at 105°C for 2 hours, and there is no curling phenomenon.

3. The functionalized membrane material according to claim 2, characterized in that, The boehmite is linear with an aspect ratio of (5-10):1 and a particle size of 1-5 μm; the alumina is spherical with a particle size of 0.5-3 μm.

4. The functionalized membrane material according to any one of claims 1-3, characterized in that, The copper powder from step (1) is activated; And / or, the solvent of the 2,4,6-methacrylate tribromophenyl ester solution in step (1) is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide and chloroform; And / or, the solvent of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution in step (1) is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, toluene, benzene and xylene; And / or, the organic solvent 1 in step (2) includes: N,N-dimethylformamide and / or dimethyl sulfoxide; And / or, the molar ratio of copper powder: tribromophenyl 2,4,6-methacrylate: 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt: PTF-Li: p-fluorophenol methacrylate: triethylene glycol monomethyl ether methacrylate is 1:(1.5~2.5):(1.1~1.3):1:(1.8~2.2):(1.8~2.2).

5. The functionalized membrane material according to any one of claims 1-3, characterized in that, The solvent for the p-bromophenol methacrylate solution in step M1 is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, and chloroform. And / or, the solvent of the 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt solution in step M1 is at least one of dichloromethane, 1,2-dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, toluene, benzene and xylene; And / or, the organic solvent 2 in step M2 includes: N,N-dimethylformamide and / or dimethyl sulfoxide.

6. A method for preparing a functionalized membrane material according to any one of claims 1-5, characterized in that, Includes the following steps: Dispersant 1 and the first protective material are added to water in S1. After stirring, the mixture is coated onto the surface of the base film and the moisture is dried to obtain a base film material covered with the first protective material. S2, the second protective material, and dispersant 2 are stirred and mixed, then coated onto the base film material covering the first protective material. After drying, the product is obtained.

7. The preparation method according to claim 6, characterized in that, The dispersant 1 comprises: polyethylene glycol and / or polyvinylpyrrolidone; And / or, the dispersant 2 comprises at least one of: sodium methylene bis(naphthalene) sulfonate, polyvinylpyrrolidone, and methylnaphthalene sulfonate formaldehyde condensate; And / or, the molar ratio of copper powder: p-bromophenol methacrylate: 2-(2-iodo-tetrafluoroethoxy)tetrafluoroethylthioyl lithium salt: PUF-Li: p-fluorophenol methacrylate: triethylene glycol monomethyl ether methacrylate is 1:(1.5~2.5):(1.1~1.3):1:(1.8~2.2):(1.8~2.2).

8. A lithium-ion battery, characterized in that, include: The functionalized membrane material according to any one of claims 1-5 or the functionalized membrane material prepared by the preparation method according to claim 6 or 7.

9. The lithium-ion battery according to claim 8, characterized in that, The lithium-ion battery is a 5Ah specification, and its DC internal resistance (DCR) is 5-10 mΩ lower than that of a lithium-ion battery with the same specification using a polypropylene base film without a protective material layer at 25℃ and 50% SOC. After 1000 charge-discharge cycles at 1C, the battery capacity retention rate is ≥87%.

10. The application of the functionalized membrane material according to any one of claims 1-5 or the functionalized membrane material prepared by the preparation method according to claim 6 or 7 in lithium-ion batteries for electric vehicles and portable electronic devices.

Citation Information

Patent Citations

  • Composite slurry, lithium battery diaphragm as well as preparation method and application of lithium battery diaphragm

    CN112234314A

  • Membrane based on fast ion conductor and preparation method and application thereof

    CN120749356A